Peningkatan Pemahaman Digital Marketing para Pelaku UMKM Kecamatan Sanrobone Kabupaten Takalar - Hasbiyadi Hasbiyadi; Andi Sulfati; Edy Jumadi; Ruslan Ahmad; Marwah Yusuf; Erniwaty Madya; Muhammad Tafsir (Jurnal Nusantara Berbakti, 2023)
The aim of this training activity is to increase the knowledge and abilities of MSME business actors in the field of digital marketing. This digital marketing socialization activity was carried out in Sanrobone village, Takalar district, which was the result of collaboration between the Sanroboe village government and STIEM Bongaya Makassar. This community service uses a participatory approach. Method of delivering material in the form of lectures. The speaker uses the lecture form to deliver the activity material, then continues with a discussion. This activity was attended by 15 MSME players. The observation results are that most MSME entrepreneurs have not done digital marketing well. There are several obstacles in managing MSMEs, namely human resource capabilities are still low, the market share of goods/services produced by MSMEs is still limited, lack of capital, and not having a good bookkeeping system. as well as a lack of understanding by the perpetrators. Follow-up activities are expected to be more technical in the form of training and technical guidance related to Digital Marketing for MSME development, both manually and application-based.